STUDY OF WAVE TRANSFORMATION AT COASTLINE CHANGE IN MENDALOK, SUNGAI KUNYIT SUB-DISTRICT, MEMPAWAH REGENCY, WEST KALIMANTAN - Kurniawan, Rahmat; Danial, Mochammad Meddy; Lestari, Arfena Deah; Meirany, Jasisca; Pratiwi, Riyanny (Jurnal Teknik Sipil, 2022)
As one of the coastal areas, Mendalok, Sungai Kunyit sub-District, Mempawah Regency faces problems caused by coastline changes such as administrative area changes and damage to the mangrove forest ecosystem in the region. The objective of this study is to determine the process of wave conversion leading to coastline changes and to determine the potential for coastline changes from 2021 to 2031. Coastline change modelling analysis is performed with the CEDAS-NEMOS application. The results showed that the wave movement pattern was dominated by the southwest and west with a significant wave height averaging 1.36 meters and the waves were broken with a wave angle of 208.09o. The result of the coastline change modelling shows that coastline changes are more dominant in the study area when experiencing abrasion with calibration values of K1 0.5 and K2 0.25. Predicting the coastline changes that will occur from 2021 to 2031 shows that the coast with the greatest abrasion value of 31.83 meters and some accretion is more dominant with the greatest accretion value of 11.21 meters.